Design and setup of intermittent-flow respirometry system for aquatic organisms - Svendsen, M. B. S.; Bushnell, P. G.; Steffensen, J. F. (Journal of fish biology, 2016)
Intermittent‐flow respirometry is an experimental protocol for measuring oxygen consumption in aquatic organisms that utilizes the best features of closed (stop‐flow) and flow‐through respirometry while eliminating (or at least reducing) some of their inherent problems. By interspersing short periods of closed‐chamber oxygen consumption measurements with regular flush periods, accurate oxygen uptake rate measurements can be made without the accumulation of waste products, particularly carbon dioxide, which may confound results. Automating the procedure with easily available hardware and software further reduces error by allowing many measurements to be made over long periods thereby minimizing animal stress due to acclimation issues. This paper describes some of the fundamental principles that need to be considered when designing and carrying out automated intermittent‐flow respirometry (e.g. chamber size, flush rate, flush time, chamber mixing, measurement periods and temperature control). Finally, recent advances in oxygen probe technology and open source automation software will be discussed in the context of assembling relatively low cost and reliable measurement systems.